Genome-wide search for exonic variants affecting translational efficiency - Li, Quan (2013)
The search for expression quantitative trait loci (eQTL) has traditionally centered entirely on the process of transcription, whereas variants with effects on mRNA translation have not been systematically studied. Here we present a high throughput approach for measuring translational cis-regulation in the human genome. Using ribosomal association as proxy for translational efficiency of polymorphic mRNAs, we test the ratio of polysomal/nonpolysomal mRNA level as a quantitative trait for association with single-nucleotide polymorphisms on the same mRNA transcript. We identify one important ribosomal-distribution effect, from rs1131017 in the 5’UTR of RPS26 , that is in high linkage disequilibrium (LD) with the 12q13 locus for susceptibility to type 1 diabetes. The effect on translation is confirmed at the protein level by quantitative Western blots, both ex vivo and after in vitro translation. Our results are a proof-of-principle that allelic effects on translation can be detected at a transcriptome-wide scale.